A Conceptual Framework of Supply Chain Management Practices and Operational Performances in Readymade Garments Industry of Bangladesh - AHM Yeaseen Chowdhury; Nazrul Islam (International Journal of Supply Chain Management, 2021)
The Supply Chain Management (SCM) has emerged as a new field of study which received much attention by the business houses and the researchers. Research shows that efficient SCM ensures on time arrival of raw materials at the production plant, prevents the need to source additional materials from alternative sources, avoids higher prices and guarantees higher profitability for the manufacturing company. This research develops a conceptual framework of the impact of SCM practices on operational performance in RMG industry of Bangladesh through literature review. In this study, six most important SCM practices and eight metrics for operational performances have been adapted from the prior literatures. This study found that there is a positive relationship between SCM practices and operational performances of RMG companies in Bangladesh.